Evaluation and Assessment of Resiliency of Transportation Networks in Ilam City - pakzad azadkhani; Mohammad salavrzizadeh; afsaneh shahmoradian (تحقیقات کاربردی علوم جغرافیایی)
Transportation and urban transportation policies are one of the most important tools which can be utilized for the qualitative and quantitative development of cities. Various factors can affect urban transportation systems including natural, economic, social, and cultural factors. the main objective of the current study is to evaluate and assess the resiliency of urban transportation networks in Ilam City, which is carried out using a descriptive-analytical and comparative method. The required information for the current study was obtained using library and field studies. The statistical population of the study included experts in urban management and crisis management, among which 40 participants were selected using convenience-based method and questionnaire was distributed among them. The analysis of the data was carried out using analytical hierarchy process (AHP) and integrated digital layers in Expert Choice and ArcGIS software applications. The results indicate that 49 percent of the transportation networks in Ilam City, which have a high level of resiliency based on the general criteria, are in high danger of flooding. Moreover, 72 percent of the traffic congestion points in Ilam City are located on streets with a high level of resiliency based on the general criteria. Among all the urban roads and streets in Ilam City, only 63 km has high levels of resiliency and these are mostly the main streets of Ilam City. The final results of the study show that improving the urban transportation system of Ilam City not only involves the structural issues of the roads, but it also involves a large number of administrative issues. Therefore, first we have to identify dangerous areas and then try to take the necessary measures through appropriate management decision making in order to improve these urban transportation networks.